Prediction of Enjoyment in School Physical Education - Gråstén, Arto (Asist Group, 2012)
The specific aim of this study was to examine whether motivational climate, perceived physical competence, and exercise motivation predict enjoyment in school physical education within the same sample of adolescents across three years of secondary school. A sample of 639 students (girls = 296, boys = 343) aged between 13- to 15-years at the commencement of the study completed the Intrinsic Motivation Climate in Physical Education Questionnaire, Physical Self-Perception Profile, Physical Education Motivation Scale, and Physical Education Enjoyment Scale. Results derived from path analyses indicated that task-involving motivational climate predicted enjoyment in physical education via perceived physical competence and intrinsic motivation in both girls and boys. In particular, these results supported previous findings of Vallerand et. al (1997) with the self-determination theory and the achievement goal theory. Ego-involving climate was not a significant predictor either in girls or boys. The current results provide continuing support for the investigation of Vallerand's model in the physical education setting, and highlight that motivational climate is an area that requires further evaluation as a contributing factor in the improvement of physical education teaching. A better understanding of the role of motivational climate may assist efforts to promote children's and adolescents' perceived physical competence, intrinsic motivation, and enjoyment in the school physical education setting.